2013
DOI: 10.1039/c2dt32174b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a versatile organometallic pro-drug (CORM) for experimental CO based therapeutics

Abstract: The complex fac-[Mo(CO)3(histidinate)]Na has been reported to be an effective CO− Releasing Molecule in vivo, eliciting therapeutic effects in several animal models of disease. The CO releasing profile of this complex in different settings both in vitro and in vivo reveals that the compound can readily liberate all of its three CO equivalents under biological conditions. The compound has low toxicity and cytoxicity and is not hemolytic. CO release is accompanied by a decrease in arterial blood pressure followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 54 publications
(118 reference statements)
1
49
0
1
Order By: Relevance
“…It turned out that isonitriles were the ligands of choice, and the correct selection of peripheral functional groups indeed led to the desired tissue selectivity. Furthermore, for a related molybdenum(0) compound, Na[Mo(histidinate)(CO) 3 ], it was shown that this is finally metabolized to a polyoxomolybdate cluster [PMo 12 O 40 ] 3− , as demonstrated by X‐ray crystallography of this species bound to lysozyme (Seixas et al ., ). Thus, instead of somewhat arbitrarily preparing and screening further metal carbonyl complexes, there is a very clear need for compounds that are designed for a very particular biomedical application and thoroughly examined not only for their CO release behaviour, but also the follow‐up products.…”
Section: Corms: Important Lead Structures and Novel Developmentsmentioning
confidence: 97%
“…It turned out that isonitriles were the ligands of choice, and the correct selection of peripheral functional groups indeed led to the desired tissue selectivity. Furthermore, for a related molybdenum(0) compound, Na[Mo(histidinate)(CO) 3 ], it was shown that this is finally metabolized to a polyoxomolybdate cluster [PMo 12 O 40 ] 3− , as demonstrated by X‐ray crystallography of this species bound to lysozyme (Seixas et al ., ). Thus, instead of somewhat arbitrarily preparing and screening further metal carbonyl complexes, there is a very clear need for compounds that are designed for a very particular biomedical application and thoroughly examined not only for their CO release behaviour, but also the follow‐up products.…”
Section: Corms: Important Lead Structures and Novel Developmentsmentioning
confidence: 97%
“…After CO release and ligand dissociation, cascades followed by oxidation processes, molybdenum-based CORMs end up as phosphomolybdate [PMo 12 O 40 ] 3− ; an X-ray structure determination showed the adduct formation of this anion with lysozyme via a hydrogen-bridge network. 170 …”
Section: Controlled Release Of Comentioning
confidence: 99%
“…However, few studies have assessed this matter. The complex fac ‐Na[Mo(histidinato)(CO) 3 ] (ALF186) has proven to be a good model for the study of some fundamental interactions of organometallic complexes with biological media 38. Triggered by O 2 , ALF186 immediately releases all of its CO equivalents, which are then transported in the systemic circulation, bound or unbound, to hemoglobin.…”
Section: Current Limitations For the Clinical Use Of Cormsmentioning
confidence: 99%